Analysis some of chemical pesticides by species of Aspergillus spp. fungi in soils and various organic fertilizers - Ali, Sadeq Mohammed; Allobawi, Salwan A. Zahra Jabbar; Alshafiee, Adeeb Kitab Abid Zaid; Sabory, Huseein Rasem (Journal of Kerbala for Agricultural Sciences, 2018)
This study aimed to analyzing some pesticide residues using Aspergillus species ,five types of chemicah pesticides are used ;fungicides (Ridomil Gold, Esther Aster and Nomolt ,(Insecticides) Chevalier and Palace Paalas ) Herbicides which are used in the controlling some pests of wheat where the effect of pesticides on the solid and liquid agricultural mediums was measured (PDA and PDB) the results showed that the herbicide Chevalier has significant differences on the fungus( A.parasiticus,A.flavus.) ,where the percentage of inhibition (100.00)%, respectively while solid medium ,The rates of inhibition of growth of fungal mass were in the broth medium( 17.69 ,97.97) respectively ,However the herbicide Paalsa has significant impact on the fungi(A.terres.) ,Where the percentage of inhibition (98.60) % in the solid medium , the percentage of inhibition of the fungal mass growth was reached( 7.50)% .